2020
DOI: 10.1182/blood.2020006158
|View full text |Cite
|
Sign up to set email alerts
|

TP53 mutations in myelodysplastic syndromes and secondary AML confer an immunosuppressive phenotype

Abstract: Somatic gene mutations are key determinants of outcome in patients with myelodysplastic syndromes (MDS) and secondary AML (sAML). In particular, patients with TP53 mutations represent a distinct molecular cohort with uniformly poor prognosis. The precise pathogenetic mechanisms underlying these inferior outcomes have not been delineated. Here we characterize the immunological features of the malignant clone and alterations in the immune microenvironment in TP53 mutant and wild type MDS and sAML patients. Notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 50 publications
(66 reference statements)
7
118
0
Order By: Relevance
“…In addition, another study presented data demonstrating that patients with TP53 mutations exhibited a reduced number of helper T cells, but a significant increase in Treg and MDSC. These results suggest that the tumor microenvironment (TME) of TP53 mutated MDS and sAML might display an immune escape phenotype [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study presented data demonstrating that patients with TP53 mutations exhibited a reduced number of helper T cells, but a significant increase in Treg and MDSC. These results suggest that the tumor microenvironment (TME) of TP53 mutated MDS and sAML might display an immune escape phenotype [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TP53 clones expand over time and drive transformation to t-MN, being the bulk of the malignant clone at diagnosis [61]. This intrinsic advantage may be related to a specific TP53-related immune escape phenotype, as shown by a recent study where TP53 mutant cases showed an imbalance of checkpoint molecules and expansion of highly immunosuppressive regulatory T cells and myeloid-derived suppressor cells [62] (Figure 2). PPM1D is the second most frequently mutated gene, accounting for 20% of t-MN cases and, as mentioned, it has been linked to previous cancer treatment exposure [63].…”
Section: The Case Of Tp53 and Ppm1d In Therapy-related Chipmentioning
confidence: 93%
“…The role of the CSC niche in modulating the level of tumor immunity is of great interest. TP53 mutations in myelodysplastic syndromes and secondary AML patients confer an immunosuppressive phenotype (Sallman et al, 2020). Those TP53 mutant patients display significantly reduced numbers of cytotoxic T lymphocytes (CTLs) and helper T cells, as well as decreased NK cells with increased regulatory T cells (Treg cells) and myeloid-derived suppressor cells (MDSCs) (Sallman et al, 2020).…”
Section: Infiltrated Immune Cellsmentioning
confidence: 99%
“…TP53 mutations in myelodysplastic syndromes and secondary AML patients confer an immunosuppressive phenotype (Sallman et al, 2020). Those TP53 mutant patients display significantly reduced numbers of cytotoxic T lymphocytes (CTLs) and helper T cells, as well as decreased NK cells with increased regulatory T cells (Treg cells) and myeloid-derived suppressor cells (MDSCs) (Sallman et al, 2020). Notably, downregulation of miR-34a was observed in TP53 mutant patients (Sallman et al, 2020), suggesting a close link between miR-34a expression levels, p53 mutation status, and tumor immunity.…”
Section: Infiltrated Immune Cellsmentioning
confidence: 99%